The development of a harmonized pan-European charging infrastructure for Electric Vehicles:Policy- Initiative interaction between EU and Member States - Collado, Magda A (My University, 2013)
Electric Vehicles have been appointed as a means of decarbonizing the personal transport sector without curbing mobility. A charging network that addresses driving range, allowing for extended circulation, must support this emerging technology. Unfortunately, lack of stable policy framework has led to the development of a heterogeneous charging technology of incompatible connector plugs, vehicle inlets and charging standards. The recently proposed EU Directive (COM (2013) 18) on the Deployment of Alternative Fuel Infrastructure addresses this technology and market fragmentation by setting Charge Point targets and standardizing plug types. The main aim of this thesis is to examine how current policies and initiatives in individual Member State are achieving EU policy objectives for a harmonized Pan-‐European charging network for EVs. The study uses an innovative method for policy analysis, the Balance Scorecard (BSC), which had to be adapted from its original framework. The complimentary aim of this thesis is to modify the BSC method and explore its utility for policy analysis. Three Member States and their capitals are used as study cases: Germany-‐Berlin, The United Kingdom-‐London and Sweden-‐Stockholm. The cases provide a good combination of charge point requirements and local automotive industry presence. Results show selected cases meet 69% of the Directive’s requirements. Germany and The UK both have defined policy for charging infrastructure, not so Sweden. Different policy approaches have led to different charging infrastructure characteristics, with Germany having the highest standardization. The standard Type 2 Connector is offered in 95% of the Fast Charge Points, but only in 25% and 0% of Slow and Fast DC Charge Points respectively. Having different Payment methods was identified as hindering public accessibility. German and UK existing national policy will have to be adapted to increase the targeted amount of Charge Points and ensure their common technical specifications. Sweden can formulate a policy that complies with requirements from the beginning. The BSC proved utility as multidimensional policy analysis method, aligning strategy and objectives between EU and Member States. The biggest strength is the systematic framework that allows for comparison between varying cases. The framework has Benchmarketing possibilities to study different cases of electromobility (e.g. EU leaders and laggards, or between EU, USA, Chinese cities.
Keywords: Annan naturvetenskap; Other Natural Sciences